Role of Mass Media in Using Antenatal Care Services among Pregnant Women in Bangladesh - Rawnaq Ara Parvin; Md. Faisal-; Md. Belal Hossain (CV. Literasi Indonesia, 2022)
The purpose of this study is to measure the predicting factors which can play a role of mass media in using the Antenatal Care Services (ANC) for pregnant women. The mixed-method strategy is followed in this study. 50 women were selected based on a convenient sampling technique to gather survey data including open and closed-ended responses. A frequency table was carried out to generate the study findings. Along with this, a few case studies were taken to support the quantitative findings so that the outcomes proved a more solid investigation. The study findings showed that there was a positive linkage between media programs and the ANC status of rural women. Pregnant women will get a clear view of how they should be more aware when they are in complications and how they will take advice from mass media pre-post delivery period.